2020
DOI: 10.22190/fueo200801022a
|View full text |Cite
|
Sign up to set email alerts
|

Oil Price Shocks and Macroeconomic Performance of the Nigerian Economy: A Structural Var Approach

Abstract: This study examines the effect of oil price shocks on the macroeconomic performance of the Nigerian economy covering the period from 1980 to 2018. The effect of oil price shocks is investigated on macroeconomic variables like output growth, inflation, interest rate, exchange rate and industrial production index using the structural vector autoregression (SVAR) approach. The results of the investigation reveal that oil price shocks have significantly and negatively affected economic growth and industrial output… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…While shedding more light on the nexus between commodity price fluctuations in some commodity-dependent African countries, the result of the structured VAR and descriptive analysis by [5] showed a heterogeneous relationship between shocks from commodity products and economic activities of the countries under investigation. Aligning with this was the study by [13] in Nigeria, using the S-VAR technique of estimation. The study concluded that shocks from oil price affect output and growth significantly and negatively.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…While shedding more light on the nexus between commodity price fluctuations in some commodity-dependent African countries, the result of the structured VAR and descriptive analysis by [5] showed a heterogeneous relationship between shocks from commodity products and economic activities of the countries under investigation. Aligning with this was the study by [13] in Nigeria, using the S-VAR technique of estimation. The study concluded that shocks from oil price affect output and growth significantly and negatively.…”
Section: Literature Reviewmentioning
confidence: 96%
“…These raw products constitute a higher percentage of the GDP of the EAC as a region [5,11]. However, the available evidence shows that production of goods and by extension services cannot be divorced from energy resources such as oil [12,13]. In essence, shocks from oil prices will not only affect commodity outputs but also the prices in international markets.…”
Section: Introductionmentioning
confidence: 99%
“…In his study, Raymond [22] investigated the stimuli of fluctuations in oil prices on the overall economic performance of Nigeria. The analysis included the time frame spanning from 1980 to 2018.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They demonstrated with Impulse Respond Function and Forecast Error Variance Decomposition that a one-way causality exists between oil price and macroeconomic variables in Nigeria. Alenoghena (2020) examined the effect of oil price shocks on the macroeconomic performance of the Nigerian economy with a SVAR model from 1980-2018. His results revealed that oil price shocks have significant and negative impact on economic growth and industrial output in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 99%